THE INFLUENCE OF VISUAL MODELS ON THE EVALUATION OF DECISIONS IN DESIGN PRACTICE - Бердинських , С. О. (Art and Design, 2024)
Purpose. The work is to study the problem of new means of presenting three-dimensional designed forms; systematization of the main visual models at the design development stage; determination of their impact on the design assessment. Methodology. An analysis of information sources in the fields of research of design methods; tools for shaping architectural objects, industrial design and environmental design; structural and systemic methods were used; and synthesis of research results was carried out. Results. The study has proven that in the system of design practice, priority is given to models that create a complex three-dimensional impression that can more objectively inform about the properties of the object. These include physical scale models, as well as virtual digital 3D prototypes, interaction with which is based on the principles of interactivity using screen and VR technologies. It is noted that, however, the role of traditional graphic models, in particular orthogonal projections, does not decrease, but, on the contrary, gains new opportunities, when used simultaneously with the latest arsenal of design tools. Scientific novelty. This study contributes to the field of design by synthesizing the potential of traditional methods for evaluating design results with advanced visualization technologies. It highlights the potential for integrating tools for rational and sensory evaluation to expand strategies for addressing design challenges. Practical significance. The obtained results can be applied in design practice, in the educational process of training specialists in artistic and creative fields, and in further research in art history, cultural studies, architecture, and design.